Robotics to promote elementary education pre-service teachers' STEM engagement, learning, and teaching. (15th December 2015) - Kim, ChanMin; Kim, Dongho; Yuan, Jiangmei; Hill, Roger B.; Doshi, Prashant; Thai, Chi N.
Abstract: We report a research project with a purpose of helping teachers learn how to design and implement science, technology, engineering, and mathematics (STEM) lessons using robotics. Specifically, pre-service teachers' STEM engagement, learning, and teaching via robotics were investigated in an elementary teacher preparation course. Data were collected from surveys, classroom observations, interviews, and lesson plans. Both quantitative and qualitative data analyses indicated that pre-service teachers engaged in robotics activities actively and mindfully. Their STEM engagement improved overall. Their emotional engagement (e.g., interest, enjoyment) in STEM significantly improved and in turn influenced their behavioral and cognitive engagement in STEM. Their lesson designs showed their STEM teaching was developing in productive directions although further work was needed. These findings suggest that robotics can be used as a technology in activities designed to enhance teachers' STEM engagement and teaching through improved attitudes toward STEM. Future research and teacher education recommendations are also presented. Highlights: The preparation of elementary teachers to teach STEM via robotics was studied. Integrative STEM education was highlighted. The lens of engagement theory was used to examine teacher learning and performance. Productive struggles while learning to program were showcased. The potential of robotics to enhance teachers' STEM engagement and teaching is discussed.